ANALISIS NILAI TAMBAH DAN TINGKAT KESEJAHTERAAN PETANI AREN DI DESA SARANG TIUNG KECAMATAN PULAU LAUT SIGAM KABUPATEN KOTABARU - Ika Agustin; Arfa Agustina Rezekiah; Eko Rini Indrayatie (Universitas Lambung Mangkurat, 2026)
Demand for palm sugar on the market is increasing because consumers are satisfied with its quality. This research aims to analyze the added value and level of welfare of sugar palm farmers in Sarang Tiung Village, Pulau Laut Sigam District, Kotabaru Regency, South Kalimantan Province. The approach used in this research is quantitative and qualitative, with data collection techniques through observation, interviews and documentation. Primary data was obtained from surveys and interviews with sugar palm farmers, while secondary data came from literature and related agencies. Respondents in this study were selected using purposive sampling, with a total of 30 sugar palm farmers. Data analysis was carried out using the Hayami method and descriptive quantitative methods to describe the conditions and situations from the interview results. The research results show that the added value ratio of the palm sugar business is 42.70%, which is included in the high category, and the level of farmer welfare according to GSR is 0.69, which means the level of welfare of palm sugar farmers is in the more prosperous category